Pemberdayaan Masyarakat Pemanfaatan Limbah Pelepah Pisang Untuk Meningkatkan Ekonomi Masyarakat (Desa Marga Mulya Kec. Bumi Agung Kab. Lampung Timur) - Atika Riasari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
This empowerment was carried out bearing in mind that there are still many banana tree fronds that are not used and only become waste, therefore to overcome the large amount of banana frond waste in Marga Mulya Village. And to find out what the benefits of banana fronds are for processed products that are useful and have economic value, we make use of these banana fronds by making processed banana fronds chips that have high economic power by empowering housewives in Marga Mulya Village. This community empowerment is carried out every Saturday with four meetings. And it is hoped that the manufacture of banana chips which has been implemented in Marga Mulya Village can continue and help the economy of local residents.